2016
DOI: 10.3109/10409238.2015.1128875
|View full text |Cite
|
Sign up to set email alerts
|

The expanding repertoire of receptor activity modifying protein (RAMP) function

Abstract: Receptor activity modifying proteins (RAMPs) associate with G-protein-coupled receptors (GPCRs) at the plasma membrane and together bind a variety of peptide ligands, serving as a communication interface between the extracellular and intracellular environments. The collection of RAMP-interacting GPCRs continues to expand and now consists of GPCRs from families A, B, and C, suggesting that RAMP activity is extremely prevalent. RAMP association with GPCRs can regulate GPCR function by altering ligand binding, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 58 publications
1
36
0
Order By: Relevance
“…The steps in the lifecycle of GPCR include desensitization, endocytosis, internalization, resensitization, recycling, degradation and down‐regulation , and we propose that soy protein can modify some of these lifecycle processes of the GR in WAT. Christopoulos et al demonstrated that RAMP2 interacts with the GR , whereas Weston et al showed that this interaction increased both the ligand selectivity and G protein preference of the GR .…”
Section: Discussionmentioning
confidence: 99%
“…The steps in the lifecycle of GPCR include desensitization, endocytosis, internalization, resensitization, recycling, degradation and down‐regulation , and we propose that soy protein can modify some of these lifecycle processes of the GR in WAT. Christopoulos et al demonstrated that RAMP2 interacts with the GR , whereas Weston et al showed that this interaction increased both the ligand selectivity and G protein preference of the GR .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this mouse may also facilitate studies on the biological role of the AMY 1 receptor in the biology and migraine pathogenesis of CGRP and possibly amylin. Finally, because RAMP1 is associated with multiple receptors, such as the VIP/PACAP receptors (Hay et al, ; Klein et al, ), these mice may also be useful for testing non‐CGRP‐based therapies. In conclusion, the global hRAMP1 mice may be useful for future development and screening of migraine therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…However, GPCRs are increasingly found in complex with extracellular binding partners (Knapp and Wolfrum, 2016). One such example involves receptor activity-modifying proteins, which interact with both the transmembrane and extracellular domains of various GPCRs in cis to modulate signaling and trafficking processes by well established mechanisms (Hay and Pioszak, 2016;Klein et al, 2016). Intriguingly, recent studies have begun to identify additional GPCR interactions with secreted extracellular proteins, extracellular matrix (ECM) components, and adhesion molecules or multimeric complexes across cellular junctions, or transcellularly.…”
Section: The Emerging Extracellular Dimension Of G Protein-coupledmentioning
confidence: 99%